Quality of antenatal care and associated factors in a rural county in Kenya: an assessment of service provision and experience dimensions - Patience A. Afulani; Laura Buback; Francisca Essandoh; Joyceline Kinyua; Leah Kirumbi; Craig R. Cohen (BMC, 2019)
Abstract Background This study aimed to assess the quality of antenatal care (ANC) women received in Migori county, Kenya-including both service provision and experience dimensions-and to examine factors associated with each dimension. Methods We used survey data collected in 2016 in Migori county from 1031 women aged 15-49 who attended ANC at least once in their most recent pregnancy. ANC quality service provision was measured by nine questions on receipt of recommended ANC services, and experience of care by 18 questions on information, communication, dignity, and facility environment. We summed the responses to the individual items to generate ANC service provision and experience of care scores. We used both linear and logistic regression to examine predictors. Results The average service provision score was 10.9 (SD = 2.4) out of a total of 16. Most women received some recommended services once, but not at the frequency recommended by the Kenyan Ministry of Health. About 90% had their blood pressure measured, and 78% had a urine test, but only 58 and 14% reported blood pressure monitoring and urine test, respectively, at every visit. Only 16% received an ultrasound at any time during ANC. The average experience score is 27.3 (SD = 8.2) out of a total score of 42, with key gaps demonstrated in communication. About half of women were not educated on pregnancy complications. Also, about one-third did not often understand the purposes of tests and medicines received and did not feel able to ask questions to the health care provider. In multivariate analysis, women who were literate, employed, and who received all their ANC in a health center had higher experiences scores than women who were illiterate (coefficient = 1.52, CI:0.26,2.79), unemployed (coefficient = 2.73, CI:1.46,4.00), and received some ANC from a hospital (coefficient = 1.99, CI: 0.84, 3.14) respectively. The wealthiest women had two times higher odds of receiving an ultrasound than the poorest women (OR = 2.00, CI:1.20,3.33). Conclusion Quality of ANC is suboptimal in both service provision and experience domains, with disparities by demographic and socioeconomic factors and facility type. More efforts are needed to improve quality of ANC and to eliminate the disparities.